Contraception After Delivery Among Publicly Insured Women in Texas: Use Compared With Preference. Issue 2 (August 2017) - Potter, Joseph E.; Coleman-Minahan, Kate; White, Kari; Powers, Daniel A.; Dillaway, Chloe; Stevenson, Amanda J.; Hopkins, Kristine; Grossman, Daniel
Abstract : OBJECTIVE: To assess women's preferences for contraception after delivery and to compare use with preferences. METHODS: In a prospective cohort study of women aged 18–44 years who wanted to delay childbearing for at least 2 years, we interviewed 1, 700 participants from eight hospitals in Texas immediately postpartum and at 3 and 6 months after delivery. At 3 months, we assessed contraceptive preferences by asking what method women would like to be using at 6 months. We modeled preference for highly effective contraception and use given preference according to childbearing intentions using mixed-effects logistic regression testing for variability across hospitals and differences between those with and without immediate postpartum long-acting reversible contraception (LARC) provision. RESULTS: Approximately 80% completed both the 3- and 6-month interviews (1, 367/1, 700). Overall, preferences exceeded use for both—LARC: 40.8% (n=547) compared with 21.9% (n=293) and sterilization: 36.1% (n=484) compared with 17.5% (n=235). In the mixed-effects logistic regression models, several demographic variables were associated with a preference for LARC among women who wanted more children, but there was no significant variability across hospitals. For women who wanted more children and had a LARC preference, use of LARC was higher in the hospital that offered immediate postpartum provision ( P <.035) as it was for U.S.-born women (odds ratio [OR] 2.08, 95% CI 1.17–3.69) and women with public prenatal care providers (OR 2.04, 95% CI 1.13–3.69). In the models for those who wanted no more children, there was no significant variability in preferences for long-acting or permanent methods across hospitals. However, use given preference varied across hospitals ( P <.001) and was lower for black women (OR 0.26, 95% CI 0.12–0.55) and higher for U.S.-born women (OR 2.32, 95% CI 1.36–3.96), those 30 years of age and older (OR 1.82, 95% CI 1.07–3.09), and those with public prenatal care providers (OR 2.04, 95% CI 1.18–3.51). CONCLUSION: Limited use of long-acting and permanent contraceptive methods after delivery is associated with indicators of health care provider and system-level barriers. Expansion of immediate postpartum LARC provision as well as contraceptive coverage for undocumented women could reduce the gap between preference and use. Abstract : Preference for long-acting and permanent contraceptive methods exceeds their use after delivery by public patients in Texas, in part as a result of health care provider and system-level barriers.